PENERAPAN MODEL PEMBELAJARAN ASSURE TERHADAP KEMAMPUAN LITERASI MATEMATIS PADA PESERTA DIDIK KELAS V SEKOLAH DASAR - Nurhalisza, Nurhalisza; Yuhana, Yuyu; Alamsyah, Trian Pamungkas (STKIP Persada Khatulistiwa Sintang, 2024)
This research aims to find out whether the Mathematical Literacy of students who receive learning using the Assure model is better than those who receive learning using the Problem Based Learning model. This research is a quasi-experimental research with the subjects of this research being students in classes 5A and 5B at SDN Anyar 2 with 27 students in each class. This research uses test instruments to measure students' mathematical literacy and non-test instruments using interviews and observations. This research data analysis technique uses descriptive statistics on the Pretest and Posttest. The research results showed that in the pretest, experimental class students got an average of 50.4 and the control class 49.12 and there was almost no difference in initial ability. Posttest results showed that the experimental class was superior with an average score of 78 and the control class 63.85. This shows that the mathematical literacy skills of experimental class students who were given the Assure model improved better than students who were given the Problem Based Learning model.